Description of students learning motivation towards the use of phet simulation in physics online learning in terms of self-efficacy and anxiety levels - Ilham Eka Prasetya; Muhammad Yusuf; Trisnawaty Junus Buhungo (Jurnal Pijar Mipa, 2022)
This study aims to describe students' motivation to use PhET Simulation in online learning physics in class XI Science at SMA Terpadu Wira Bhakti Gorontalo regarding self-efficacy and anxiety levels. This type of research is descriptive qualitative. The research subjects were nine class grade eleventh IPA 1 SMA Terpadu Wira Bhakti Gorontalo with high, medium, and low academic abilities. Data collection techniques using observation, questionnaires, and interviews. The data analysis technique used descriptive statistical analysis and qualitative analysis, including data reduction, data presentation, and conclusion drawing/data verification. The results of the research on student learning motivation towards the use of PhET Simulation in online learning physics showed that based on the assessment on the level of self-efficacy and anxiety is categorized as very high. Students with high (H) and moderate (M) academic abilities had high learning motivation very high category. In contrast, students with the low academic ability (L) have a high category of learning motivation. In conclusion, students become motivated in learning because of the use of PhET Simulation in online learning physics class XI IPA SMA Terpadu Wira Bhakti Gorontalo in terms of self-efficacy. Student anxiety is categorized as very high.